Introduction and history of Qur’an recitation (Qirat): قرائت قرآنیہ کا تعارف و تاریخ - Sodhar, Aijaz Ali; Ansari, Dr. Tanveer Huma; Channa, Abdul Qayoom (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Allah Almighty had sent more or less than one lac and twenty four thousand prophets (علیہم السلام) for the guidance of human beings in this world. He sent 313 of them with a new law. They are called Rasools. Allah Almighty Reveal holy books to some of them. He ended this sacred line by revealing the Holy Quran to Hazrat Muhammad (ﷺ). That whatever is to be read is what the Qur’an means. The most read book in the world is the Quran. It is read somewhere in the world every single instant of the twenty-four hours of day and night. Many of his Companions were chosen by the Prophet (ﷺ) to write the Qur’an. The Holy Prophet (ﷺ) also gave the scribes instructions to write this verse before or after a certain verse, or to write a Surah before or after a certain Surah. Thus, at the time of the Holy Prophet (ﷺ), the Qur’an was composed. The sequence of recitation at the time of the Holy Prophet (ﷺ) is the same as the order in which it is read today. This is the same order that Jibraeel (علیہ السلام) told the Prophet (ﷺ). In the year 12 AH, the Holy Quran was compiled in book form on paper. In the year 75 AH, Airabs (، اعرابsymbols) were introduced to facilitate recitation for non-Arabs. The Prophet (ﷺ) taught the Qur’an to his Companions (رضی اللہ عنہم). A large group of Companions (رضی اللہ عنہم) used to learn and teach the Holy Quran in the Prophet’s Mosque in front of the Holy Prophet (ﷺ). As a result, a large group of Companions (رضی اللہ عنہم) was formed who could memorize and teach the Holy Quran in expert manner. Thousands of Companions (رضی اللہ عنہم) learned the Qur’an directly or indirectly from the Holy Prophet (ﷺ). Some of them were known by the title of Sahaba Qura (رضی اللہ عنہم). The literal meaning of Qirat is to recite the Qur’an according to a tradition (روایت). Just as it is necessary to recite the Qur’an with Tajweed, so too it is necessary to follow the tradition for the correctness of the Qirat. It’s a permanent a lore and art. This article deals with the introduction and history of Quran recitation (Qirat).